Level of Insight in Patients With Obsessive–Compulsive Disorder: An Exploratory Comparative Study Between Patients With “Good Insight” and “Poor Insight” - de Avila, Richard Chuquel Silveira; do Nascimento, Laura Gratsch; Porto, Rafaella Landell de Moura; Fontenelle, Leonardo; Filho, Eurípedes Constantino Miguel; Brakoulias, Vlasios; Ferrão, Ygor Arzeno (Frontiers in Psychiatry, 2019)
Insight is the ability to perceive and evaluate external reality and to separate it from its subjective aspects, or the ability to self-assess difficulties and personal qualities. Insight is a predictor of success in the treatment of Obsessive Compulsive Disorder (OCD) (individuals with poor insight may become refractory to treatment). The objective of this study is to investigate factors associated with poor insight in individuals with OCD. Methods: This exploratory study compared OCD patients with good insight (n=148) to those with poor insight (n=124) according to the Brown Belief Assessment Scale (BABS) scores (null=good insight; above the 75% percentile=with poor insight); Intermediate scores were excluded. Socio-demographic characteristics, clinical and psychopathological aspects were compared in a univariate analysis. A logistic regression determined factors related to poor insight. Results: poor insight group differed from good insight individuals regarding: more prevalent use of neuroleptics (p=0.05); higher untreated time interval (p<0.001); higher total Y-BOCS score; higher obsessions and compulsions factors (all factors with p <0.001); higher DY-BOCS total and dimensional scores (p from 0.04 to 0.001); higher prevalence of contamination/cleaning(p=0.006) and hoarding (p<0.001) symptoms dimensions; more prevalent sensory phenomena (p=0.023); higher levels of depression (p=0,007); more prevalent comorbidity with Bipolar Affective Disorder (p=0.05) and Post-traumatic stress disorder (PTSD) (p=0.04). After analyzing the logistic regression, we conclude that the most important factors associated with poor insight are: the presence of any sensory phenomena (OR: 2.24), use of neuroleptics (OR: 1.66), hoarding symptoms (OR: 1.15). Conclusion: The variability of insight in patients with OCD seems to be an important psychopathological characteristic in the differentiation of possible subtypes of OCD, since the poor insight is associated with sensory phenomena and greater use of neuroleptics, which makes it possible to conjecture the role of dopaminergic neurocircuits in the neurobiology of this disorder. In addition, there is also an association with the symptoms of hoarding content, admittedly one of the symptomatic contents with less response to conventional OCD treatments. Studies based on neurobiological aspects such as neuroimaging and neuropsychology may help to elucidate more consistently the role of insight in patients with OCD and the repercussions concerning available treatments.